Effects of plyometric training on measures of physical fitness in racket sport athletes: a systematic review and meta-analysis - Deng, Nuannuan; Soh, Kim Geok; Abdullah, Borhannudin; Huang, Dandan (PeerJ, 2023)
Background Over the past decade, the popularity of racket sports has surged. Plyometric training (PT) has been the focus of extensive research because of the proven benefits it provides to athletes. However, there is a lack of systematic reviews and meta-analyses specifically evaluating the impact of PT on physical fitness metrics in racket sport athletes. This study aimed to conduct a comprehensive review and analysis of evidence derived from randomized controlled trials (RCTs) to evaluate the effects of PT on measures of physical fitness among racket sports athletes.